2009
DOI: 10.3389/neuro.05.001.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dual transneuronal tracing in the rat entorhinal-hippocampal circuit by intracerebral injection of recombinant rabies virus vectors

Abstract: Dual transneuronal tracing is a novel viral tracing methodology which employs two recombinant viruses, each expressing a different reporter protein. Peripheral injection of recombinant pseudorabies viruses has been used as a powerful method to defi ne neurons that coordinate outputs to various peripheral targets of motor and autonomic systems. Here, we assessed the feasibility of recombinants of rabies virus (RV) vector for dual transneuronal tracing in the central nervous system. First, we examined whether tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 46 publications
3
80
0
Order By: Relevance
“…By testing dual infection in vitro and in vivo, these authors have shown that the phenomenon of viral interference for replication, noted for isogenic PrV strains (see Section 2.10), is also inherent to isogenic rabies virus recombinants. In other words, when the two viruses infect the same neurons at different times, the efficiency of the second infection decreases exponentially in a time-dependent manner; thus, to achieve efficient double labeling, the two viruses must infect the same neurons within a few hours (Ohara et al, 2009). Moreover, as for PrV strains, the length of the inserted foreign genes can modify the replication and/or propagation speed of the rabies virus recombinants (Ohara et al, 2009).…”
Section: Dual Transneuronal Tracing With Isogenic Rabies Virus Recombmentioning
confidence: 99%
See 2 more Smart Citations
“…By testing dual infection in vitro and in vivo, these authors have shown that the phenomenon of viral interference for replication, noted for isogenic PrV strains (see Section 2.10), is also inherent to isogenic rabies virus recombinants. In other words, when the two viruses infect the same neurons at different times, the efficiency of the second infection decreases exponentially in a time-dependent manner; thus, to achieve efficient double labeling, the two viruses must infect the same neurons within a few hours (Ohara et al, 2009). Moreover, as for PrV strains, the length of the inserted foreign genes can modify the replication and/or propagation speed of the rabies virus recombinants (Ohara et al, 2009).…”
Section: Dual Transneuronal Tracing With Isogenic Rabies Virus Recombmentioning
confidence: 99%
“…Moreover, as for PrV strains, the length of the inserted foreign genes can modify the replication and/or propagation speed of the rabies virus recombinants (Ohara et al, 2009). While these findings stress the importance of using isogenic strains with similar propagation properties, and/or possibly the need to adjust the relative dose of each virus to achieve optimal dual transneuronal labeling, the successful colocalization of the two isogenic rabies virus mutants in vitro and in vivo, demonstrated by Ohara et al (2009) clearly illustrates the potential of genetically engineered rabies viruses for dual transneuronal tracing.…”
Section: Dual Transneuronal Tracing With Isogenic Rabies Virus Recombmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as the hippocampus forming reciprocal connections with the perirhinal cortex (Swanson and Cowan, 1977;Deacon et al, 1983;Kosel et al, 1983;Van Groen and Wyss, 1990;McIntyre et al, 1996;Kloosterman et al, 2003b), it also shows strong interconnectivity with the entorhinal (Steward, 1976;Steward and Scoville, 1976;Swanson and Cowan, 1977;Swanson et al, 1981;Wyss, 1981;Nojyo, 1993, 1995;Ohara et al, 2009) and postrhinal cortices (Kloosterman et al, 2003b). Many of these projections have been shown to be capable of eliciting an electrophysiological response in their respective tissues.…”
Section: Hippocampal and Parahippocampal Projectionsmentioning
confidence: 99%
“…Differences in anatomy, social communication and reproduction, as well as the reported morphological diversity of the VNO suggest that direct comparison between even closely related species is risky and may not be meaningful (Salazar and Sánchez Quinteiro, 2009). The limited data in marsupials generally supports the presence of a well‐developed VNO similar to that reported in Rodentia (see e.g., Tarsipes rostratus —Kratzing, 1982; Monodelphis domestica —Poran 1998; Macropus eugenii —Schneider et al, 2008; Antechinus —Toftegaard, 1998).…”
Section: Introductionmentioning
confidence: 99%